Investigating the effects of maximal anaerobic fatigue on dynamic postural control using the Y-Balance Test - Johnston, W.; Dolan, K.; Reid, N.; Coughlan, G. F.; Caulfield, B. (Journal of Science and Medicine in Sport, 2018)
Objectives: The Y Balance Test is one of the most commonly used dynamic balance assessments, providing an insight into the integration of the sensorimotor subsystems. In recent times, there has been an increase in interest surrounding it`s use in various clinical populations demonstrating alterations in motor function. Therefore, it is important to examine the effect physiological influences such as fatigue play in dynamic postural control, and establish a timeframe for its recovery. Design: Descriptive laboratory study. Methods: Twenty male and female (age 23.75 ± 4.79 years, height 174.12 ± 8.45 cm, mass 69.32 ± 8.76 kg) partaking in competitive sport, completed the Y Balance Test protocol at 0, 10 and 20 min, prior to a modified 60 s Wingate fatiguing protocol. Post-fatigue assessments were then completed at 0, 10 and 20 min post-fatiguing intervention. Results: Intraclass correlation coefficients demonstrated excellent intra-session reliability (0.976-0.982) across the three pre-fatigue YBT tests. Post-hoc paired sample t-tests demonstrated that all three reach directions demonstrated statistically significant differences between pre-fatigue and the first post-fatigue measurement (anterior; p = 0.019, posteromedial; p = 0.019 & posterolateral; p = 0.003). The anterior reach direction returned to pre-fatigue levels within 10 min (p = 0.632). The posteromedial reach direction returned to pre-fatigue levels within 20 min (p = 0.236), while the posterolateral direction maintained a statistically significant difference at 20 min (p = 0.023). Conclusions: Maximal anaerobic fatigue has a negative effect on normalised Y balance test scores in all three directions. Following the fatiguing protocol, dynamic postural control returns to pre-fatigue levels for the anterior (<10 min), posteromedial (<20 min) and posterolateral (>20 min).